Paper-based biosensors for clinical and biomedical applications: Emerging engineering concepts and challenges - Mahato K.; Purohit B.; Kumar A.; Chandra P. (My University, 2025)
In this chapter, we have discussed the advancements in the conventional diagnoses and their paradigm shift towards the affordable, sensitive, reliable, user-friendly, and deliverable diagnostics-based approaches. Among various alternatives, paper-based technologies have greatly been acclaimed for delivering sensitive biosensing. Paper being a cheaper and adequate substrate; it has been widely explored for the fabrication of biosensor determining the clinically relevant molecules/biomarkers. This chapter comprehensively describes the properties of paper-based platforms in terms of achieving the sensitive detection followed by the discussion on various adopted biosensing systems including the dipsticks, lateral flow assays (LFA), microfluidic paper-based devices (μ-PAD), and most advanced peripheral accessories assisted paper-based biosensors for clinical detections/diagnoses. Following this section, we have incorporated a brief discussion on commonly used clinical samples and their interaction/behaviour to the paper-based substrates. We have also discussed the prominent challenges associated while handling these clinical samples in the paper-based modules for achieving better analytical performances. The discussion on different strategies for addressing the persisting challenges to paper-based platforms and their recent advancements have also been incorporated to put more insights. © 2020 Elsevier B.V.